A Proposed Islamic Multidimensional Framework of Poverty: Interviews with Global Experts - Sevinç, Nurgül; Bulut, Mehmet; Bulut, Mehmet (Academy of Islamic Studies, Dept of Islamic History and Civilization, University of Malaya, 2023)
This study tests the proposed Islamic framework for defining poverty and its dimensions. The study has adopted a qualitative method of expert interviews to validate the proposed Islamic multidimensional poverty framework. Eight global experts on poverty were interviewed. The study’s main findings show that spirituality has priority over other biological, psychological, social, knowledge and material dimensions regarding the definition and measurement of poverty. Hence, spirituality will be the dimension shaping the remaining domains. This finding implies a policy change to reduce poverty, mainly focusing on solutions including and prioritising spirituality, which can be subjects of future research. There is no consensus on a certain list of poverty dimensions and measures. The extant conventional literature has taken a reductionist approach to poverty and less emphasised the non-material dimensions. Meanwhile, the literature on poverty from an Islamic perspective is mainly normative. In both cases, there is an absence of studies that have proposed encompassing dimensions of poverty and its measures. © 2023, Academy of Islamic Studies, Dept of Islamic History and Civilization, University of Malaya. All rights reserved.
The authors are grateful to the participants who took part in the study. The authors are also grateful to Prof. Mustafa Omar Mohammed and Dr. Ruslan Nagayev for their suggestions to improve this research.
Keywords: Alternative multidimensional poverty; Dimensions; Expert interview